2005
DOI: 10.1126/science.1108750
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Metabolic Syndrome in Circadian Clock Mutant Mice

Abstract: The CLOCK transcription factor is a key component of the molecular circadian clock within pacemaker neurons of the hypothalamic suprachiasmatic nucleus. We found that homozygous Clock mutant mice have a greatly attenuated diurnal feeding rhythm, are hyperphagic and obese, and develop a metabolic syndrome of hyperleptinemia, hyperlipidemia, hepatic steatosis, hyperglycemia, and hypoinsulinemia. Expression of transcripts encoding selected hypothalamic peptides associated with energy balance was attenuated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
1,770
5
32

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,239 publications
(1,869 citation statements)
references
References 25 publications
62
1,770
5
32
Order By: Relevance
“…For example, Clock/Clock mutant mice develop metabolic syndrome and obesity [64], animals with a targeted disruption of the CLOCK transcriptional partner, BMAL1 (Bmal1 −/− knockout mice) display phenotype of premature aging [65], whereas an increase in carcinogenesis has been reported specifically for Per2 mutants [66]. These examples lead to several important conclusions.…”
Section: Non-circadian Function Of Circadian Proteinsmentioning
confidence: 99%
“…For example, Clock/Clock mutant mice develop metabolic syndrome and obesity [64], animals with a targeted disruption of the CLOCK transcriptional partner, BMAL1 (Bmal1 −/− knockout mice) display phenotype of premature aging [65], whereas an increase in carcinogenesis has been reported specifically for Per2 mutants [66]. These examples lead to several important conclusions.…”
Section: Non-circadian Function Of Circadian Proteinsmentioning
confidence: 99%
“…First, it has been demonstrated that altering the expression of the clock genes that coordinate seasonal and circadian rhythms leads to changes in glucose homeostasis and features of the metabolic syndrome, including hypertriglyceridaemia and hyperleptinaemia [37,38]. Second, adipocytes have fully intact clock machinery that alters in response to daytime, and which appears to correlate with the expression of a number of other genes [35].…”
Section: Seasonal and Circadian Responses In Mammalsmentioning
confidence: 99%
“…Turek et al [15] demonstrated that Clock mutant mice are hyperphagic and develop metabolic syndrome, hyperglycaemia and hyperlipidaemia. In addition, we showed that the rhythmic expression of clock genes is blunted in the liver and visceral adipose tissues of KK-A y mice, a genetic model of type 2 diabetes [16].…”
Section: Introductionmentioning
confidence: 99%